Review of the genus Gnorimoschema Busck, 1900 (Lepidoptera, Gelechiidae) in China - Li, Houhun; Bidzilya, Oleksiy V. (Zootaxa, 2017)
Nine species of the genus Gnorimoschema are recorded from China. Five new species are described: G. cinerella sp. nov. (China: Yunnan), G. gilvella sp. nov. (China: Ningxia), G. fuscescens sp. nov. (China: Gansu, Inner Mongolia; Russia: Altai, Zabaikalskiy krai), G. rufomaculata sp. nov. (China: Ningxia and Inner Mongolia; Russia: Zabaikalskiy krai), G. piskunovi sp. nov. (China: Hebei, Shanxi). G. cinctipunctella (Erschoff, 1877) sp. rev. is removed from synonymy. Three new synonyms are established: G. mongolorum Povolný, 1969 syn. nov. of G. cinctipunctella (Erschoff, 1877), G. herbichii mongoliae Povolný, 1973 and G. herbichii kamchaticum Povolný, 1977 syn. nov. of G. herbichii herbichii (Nowicki, 1864). Data on species distribution in the Palaearctic region are supplemented with new records and revised in accordance with new taxonomic data proposed in the present contribution.